Distributional analysis of rural-urban household healthcare expenditure differentials in developing countries: evidence from Ghana - Ampaw, Samuel; Nketiah-Amponsah, Edward; Agyire-Tettey, Frank; Senadza, Bernardin (Emerald, 2020)
Equity in access to and use of healthcare resources is a global development agenda. Policy makers’ knowledge of the sources of differences in household healthcare spending is crucial for effective policy. This paper investigates the differences in the determinants of household healthcare expenditure across space and along selected quantiles of healthcare expenditure in Ghana. The determinants of rural-urban healthcare expenditure gap are also explored. Data was obtained from the sixth round of the Ghana Living Standards Survey (GLSS 6) conducted in 2013. An unconditional quantile regression (UQR) and a decomposition technique based on UQR, adjusted for sample selection bias, were applied. Findings indicate that differences in the determinants of household healthcare expenditure across space and along quantiles are driven by individual-level variables. Besides, the rural-urban health expenditure gap is greatest among households in the lower quantiles and this gap is largely driven by differences in household income per capita and percentage of household members enrolled on health insurance policies. To reduce rural-urban healthcare expenditure inequality, targeted policies should be prioritised in addition to efforts to narrow rural-urban differences in household per capita income and enrolment in health insurance policies.